Productividad, estado trófico y dinámica fitoplanctónica en la laguna Sauce Grande y su afluente homónimo (pcia. de Buenos Aires, Argentina) - Cony, Noelia Leonor (2016)
The shallow lake Sauce Grande is located in the southwest of Buenos Aires province. It is a widening of the Sauce Grande River that flows in and out of the lake. The aim of this study is to estimate for the first time the primary productivity (PP) of this lake and to contrast the physiochemical variables, phytoplankton structure and trophic status with those of its main tributary. Monthly samplings (April-September 2014) were performed in the middle basin of the river and on the coast of the lake. We recorded in situ physical and chemical parameters with a multisensor Horiba U-10. Phytoplankton samples were collected with a plankton net for the qualitative study and with plastic bottles for quantitative analysis.The greatest physicochemical differences corresponded to turbidity and conductivity with values of 581.3 NTU and 9 mS/cm for the lake and 17.7 and 1.7, for the river. The average PP in the lake was 252.1 mg C/m3.h. Cyanobacteria were the most abundant taxonomic group in both systems, although its abundance was greater in the shallow lake. The Carlson index, based on the concentration of chlorophyll a and total phosphorus, identifies the lake as eutrophic, while the river was classified as oligo-mesotrophic according to the same variables. Our results suggest that the Sauce Grande Lake is an autotrophic system with a highly productive metabolism. The remaining production becomes biomass and accumulates within the system, in the form of high levels of phytoplankton abundance, in particular a massive proliferation of Cyanobacteria.